2009
DOI: 10.1093/qjmed/hcn172
|View full text |Cite
|
Sign up to set email alerts
|

The burden of chronic disorders on hospital admissions prompts the need for new modalities of care: A cross-sectional analysis in a tertiary hospital

Abstract: The study shows a high impact of cancer on planned hospitalizations whereas cardiovascular diseases and COPD generates a high percentage of unscheduled admissions. We conclude that integrated care services including patient-oriented guidelines are strongly needed to enhance both health and managerial outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 30 publications
(36 reference statements)
3
40
0
6
Order By: Relevance
“…1 Severity of illness has been well documented to affect the likelihood of hospital readmission. 13,14 In this study, we used the All Patient Refined Diagnostic Related Groups (APR-DRG) weight that has been used in previous studies as a measure of severity of illness and predicts readmission risk. 15 For the purpose of our analyses the APR-DRG weight was categorized in deciles.…”
Section: Covariatesmentioning
confidence: 99%
“…1 Severity of illness has been well documented to affect the likelihood of hospital readmission. 13,14 In this study, we used the All Patient Refined Diagnostic Related Groups (APR-DRG) weight that has been used in previous studies as a measure of severity of illness and predicts readmission risk. 15 For the purpose of our analyses the APR-DRG weight was categorized in deciles.…”
Section: Covariatesmentioning
confidence: 99%
“…A longitudinal study about the spectrum and prevalence of multimorbidities in a population of >1600 patients with chronic obstructive pulmonary disease (COPD) over 4 years reported both gastro-oesophageal reflux disease (GORD) (18% and 20% in survivors and nonsurvivors, respectively) and liver cirrhosis (<2% each) alone [1]. A study of ∼20 000 patients aimed at assessing the impact of chronic conditions on tertiary hospital admissions revealed that the prevalence of liver cirrhosis in the COPD population was <5%, a figure close to the prevalence of COPD observed in the hepatic cirrhotic cohort [2]. A third, more modest, study of 215 patients admitted to hospital (28% diagnosed with COPD) observed no differences in the number of multimorbidities between patients with and without COPD.…”
Section: Introductionmentioning
confidence: 98%
“…The number of Americans over age 65 years will double in the first 30 years of this century [1]. Medicine has changed dramatically as well and now deals increasingly with complications of chronic diseases that often result from lifestyle choices including coronary artery disease, chronic obstructive pulmonary disease, diabetes, degenerative arthritis, and asthma [2]. The care of these and other diseases will dominate healthcare during this generation's retirement years.…”
Section: Introductionmentioning
confidence: 99%
“…The care of these and other diseases will dominate healthcare during this generation's retirement years. Today, almost half of all Americans and 75% of elderly Americans have at least one chronic health problem [2][3][4]. About 70% of those with one chronic problem have at least two chronic illnesses [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation